2006
DOI: 10.1128/jvi.00933-06
|View full text |Cite
|
Sign up to set email alerts
|

Global Structural Changes in Hepatitis B Virus Capsids Induced by the Assembly Effector HAP1

Abstract: Hepatitis B virus (HBV) is a leading cause of liver disease and hepatocellular carcinoma; over 400 million people are chronically infected with HBV. Specific anti-HBV treatments, like most antivirals, target enzymes that are similar to host proteins. Virus capsid protein has no human homolog, making its assembly a promising but undeveloped therapeutic target. HAP1 [methyl 4-(2-chloro-4-fluorophenyl)-6-methyl-2-(pyridin-2-yl)-1,4-dihydropyrimidine-5-carboxylate], a heteroaryldihydropyrimidine, is a potent HBV c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
275
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(283 citation statements)
references
References 41 publications
7
275
1
Order By: Relevance
“…Others have shown that inserting short linkers at the tip of the four-helix bundle mediates a 40°rotation of the contact domain relative to the bundle (within capsids) (23). Further, small molecules have been reported that bind to HBc and induce global structural rearrangements that impair HBV capsid formation (11)(12)(13)50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have shown that inserting short linkers at the tip of the four-helix bundle mediates a 40°rotation of the contact domain relative to the bundle (within capsids) (23). Further, small molecules have been reported that bind to HBc and induce global structural rearrangements that impair HBV capsid formation (11)(12)(13)50).…”
Section: Discussionmentioning
confidence: 99%
“…capsid assembly have inferred the existence of assembly-active (HBc Ass ) and assembly-incompetent (HBc Inc ) HBc conformations (12,13,21,24,25). However, there are few detailed insights on the thermodynamic origins of structure, allostery, and dynamics for the dimeric HBc 1-149 protomer, where structural plasticity must originate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HAPs, including Bay 41-4109, Bay 38-7690, and Bay 39-5493, were first identified to prevent the formation of the HBV capsid [20,21] . These analogues inhibited HBV replication through binding within the assembly domain of HBcAg at a site that bridged elements of the secondary …”
Section: Discussionmentioning
confidence: 99%
“…HAPs bind at a sequence of the assembly domain that is involved in forming inter-dimer contacts, whereas DHBV-derived recombinant capsids show no binding [7,20] ; therefore, HAPs did not inhibit DHBV replication in cultured cells or in a DHBV-infected duck model.…”
Section: Wwwchinapharcom Yang L Et Almentioning
confidence: 99%